2000
DOI: 10.1152/ajpregu.2000.279.5.r1599
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol prevents oxidative stress and decreases blood pressure in ovariectomized rats

Abstract: In this study, we tested whether estrogen deficiency is associated with oxidative stress and decreased nitric oxide (NO) production, which could be responsible for an increased blood pressure in ovariectomized rats. Hemodynamic studies were performed on conscious, chronically instrumented rats. Chronic estrogen replacement on ovariectomized rats lowered blood pressure approximately 13 mmHg, from 119 +/- 3 mmHg in ovariectomized rats to 106 +/- 3 mmHg in ovariectomized-treated rats; it was also accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
112
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 36 publications
16
112
0
6
Order By: Relevance
“…In our experimental model as well as in Hernández et al (17) , castration triggered a significant increase in LPO (Figure 3). We suggest that castration may have reduced the thiol groups, consistent with the significant decrease in GPx activity in C + PPVL, favoring the damage, which was evidenced by the increased LPO in this group as compared to the others.…”
Section: Histologysupporting
confidence: 85%
See 2 more Smart Citations
“…In our experimental model as well as in Hernández et al (17) , castration triggered a significant increase in LPO (Figure 3). We suggest that castration may have reduced the thiol groups, consistent with the significant decrease in GPx activity in C + PPVL, favoring the damage, which was evidenced by the increased LPO in this group as compared to the others.…”
Section: Histologysupporting
confidence: 85%
“…Borekci et al (18) demonstrated the protection of estrogen in the gastric mucosa, as other authors have demonstrated the greatest protection in the cardiovascular system in women of reproductive age compared with men the same age, for their hormonal and antioxidant activity (3,12,13,17,27) . Intact or castrated female rats were subjected to PPVL (pre-hepatic model) and then analyzed regarding the influence of castration (absence of estrogen) in PH-related changes, mainly to PHG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…After surgery, the animals received an injection of antibiotics (40 000 U/kg penicillin G procaine IM). 12 …”
Section: Ovariectomymentioning
confidence: 99%
“…Deneysel çalışmalar da OVX ile oluşturulan östrojen yoksunluğunun redoks durumunu değiştir-diğini ve bu durumda uygulanan östrojen tedavisinin oksidan stresi azalttığını düşündürmüştür (41). Ayrıca, östrojen molekülünün kimyasal yapısının da serbest radikal süpürücü olarak etki ettiği ve fenol halkasındaki A pozisyonu sayesinde oksidan hasarı engellediği öne sürülmektedir (42).…”
Section: Discussionunclassified